Optimalisasi Manajemen Konflik: Perilaku Asertif Dalam Keperawatan - Wulandari, Cicilia ika; Novieastari, Enie; Purwaningsih, Sri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Professional nursing is needed to provide quality services with assertive behavior. Assertive behavior for nurses is important because nurses work always interacting with others. The purpose of this study was to describe a description of assertive behavior in hospital nursing. Research renewal can be used to optimize conflict management, assertive behavior in nursing. The method used in this study is descriptive research with survey methods. Implementation of research starts from situation analysis, problem identification, determining priority problems, making action plans, implementation, and evaluation. The study sample involved 55 nurses who were randomly selected in the inpatient room. Sample calculation uses the Rule of Thumb formula and obtained 55 nurses. The identification results showed that there were nurses who were not assertive, namely 53% of passive nurses and 25% of nurses being aggressive. Non-assertive behavior in work can cause conflicts, such as task conflicts, communication conflicts, structural conflicts, intrapersonal conflicts, and conflicts between groups. Conflict management abilities, especially assertive techniques aim to limit and avoid violence, by encouraging positive behavioral changes for the parties involved, especially assertive behavior. Conflicts that can be managed properly can have the effect of quality nursing services. The recommendations provided are able to strengthen regulations and increase conflict management knowledge, especially assertive behavior in nursing.Keywords: Assertive, Conflict Management, Nurse